ANALISIS HUKUM TERHADAP KEBIJAKAN PEMERINTAH DALAM MEWUJUDKAN KEMAJUAN LITERASI DIGITAL DUNIA PENDIDIKAN DI PAPUA - Zulrijal Bushido Gani (JOURNAL OF LAW AND NATION, 2023)
Today's humans are inseparable from the ability of a digital object including the world of education. Therefore, to keep up with the times, the knowledge and abilities of the people along with the support of government policies will be a factor in determining the extent of the ability to realize progress in digital literacy in Papua. This research is retrospective by using a qualitative approach to analyze the results of a study. The results of the study show that in realizing the advancement of digital literacy in education in Papua requires knowledge of human resources from the community as well as government policy support, knowledge is obtained from gradual learning education which must be realized with the support of government policies, but existing policies are not implemented optimally many obstacles and problems from within and outside the government. This is an obstacle in realizing the advancement of digital literacy in the world of education in Papua and Papua is considered to have not been able to fully realize digital literacy.